Graphite nanocomposites sensor for multiplex detection of antioxidants in food - Ng, K.L.; Tan, G.H.; Khor, S.M. (Elsevier, 2017)
Butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), and tert-butylhydroquinone (TBHQ) are synthetic antioxidants used in the food industry. Herein, we describe the development of a novel graphite nanocomposite-based electrochemical sensor for the multiplex detection and measurement of BHA, BHT, and TBHQ levels in complex food samples using a linear sweep voltammetry technique. Moreover, our newly established analytical method exhibited good sensitivity, limit of detection, limit of quantitation, and selectivity. The accuracy and reliability of analytical results were challenged by method validation and comparison with the results of the liquid chromatography method, where a linear correlation of more than 0.99 was achieved. The addition of sodium dodecyl sulfate as supporting additive further enhanced the LSV response (anodic peak current, Ipa) of BHA and BHT by 2- and 20-times, respectively.